ChemInform Abstract: Crystal Structure and Magnetic Properties of SrNi2‐xSb2. Issue 48 (December 2015) - Gvozdetskyi, Volodymyr; Hlukhyy, Viktor; Gladyshevskii, Roman; Faessler, Thomas F.
Abstract: The intermetallic title phase is prepared by arc‐melting of the elements followed by annealing (1370 K for 2 h and 1070 K for 96 h).